2015
DOI: 10.5137/1019-5149.jtn.16004-15.2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cerebro-spinal fluid in collagen guide channel on sciatic nerve regeneration in rat

Abstract: ABSTRACTgaps by inserting the severed nerve stumps into the two ends of the canal (16). Some natural and synthetic substances can be shaped in structures that are able to promote nerve regeneration for example: eggshell membrane (12), silicone (31), human amnion layer (22), collagen (18), collagen-Chitosan (36).Collagen-based biomaterials have been extensively studied as a promising nerve guide (7). Since collagen is a natural material, it shows excellent biocompatibility, insignificant immunogenicity, and hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Farjah et al () have also demonstrated that cerebrospinal fluid (CSF) in collagen nerve guide channel efficiently increases nerve regeneration and promotes functional recovery in the injured sciatic nerve (10‐mm sciatic nerve gap) of rats.…”
Section: Materials For Fabricating Nerve Conduitsmentioning
confidence: 99%
“…Farjah et al () have also demonstrated that cerebrospinal fluid (CSF) in collagen nerve guide channel efficiently increases nerve regeneration and promotes functional recovery in the injured sciatic nerve (10‐mm sciatic nerve gap) of rats.…”
Section: Materials For Fabricating Nerve Conduitsmentioning
confidence: 99%
“…For the induction of varicocele, rats were anaesthetised via the administration of ketamine and xylazine at doses of 50 mg/kg BW and 10 mg/kg BW, respectively. Afterwards, varicocele was induced by a partial obstruction of the left renal vein (Farjah, Dolatkhah, Pourheidar, & Heshmatian, 2017;Turner, 2001). All experimental procedures were performed in a sterile condition.…”
Section: Procedures Of Varicocele Inductionmentioning
confidence: 99%
“…CSF from rats with amyotrophic lateral sclerosis (ALS) initiate profound cellular changes in glia to cause synaptic dysfunction (Shanmukha, Narayanappa, Nalini, Alladi, & Raju, 2018), while CSF from conditions of sepsis and meningitis directly infect glia to influence muscle contraction (Delbaz et al., 2020). Moreover, in vivo rat models of spinal cord injury have used healthy CSF to increase neuronal extension and recovery via collagen nerve guide channels (Farjah, Dolatkhah, Pourheidar, & Heshmatian, 2017). Nonetheless, the vast majority of tissue engineering studies continue to use conventional cell culture media, such as Neurobasal (NB) and Dulbecco's Modified Eagle Medium (DMEM), in the study of neural stem cells, transplantable biomaterials, and development of organotypic explants that model spinal injury and disease (Cembran, Bruggeman, Williams, Parish, & Nisbet, 2020; Tsintou, Dalamagkas, & Makris, 2020).…”
Section: Introductionmentioning
confidence: 99%